Temperament and character differences of patients with polycystic ovary syndrome - Öztürk, Ahmet; Kucur, Suna Kabil; Seven, Ali; Deveci, Erdem; Şencan, Halime; Yilmaz, Onur; Kiliç, Alperen (Journal of gynecology obstetrics and human reproduction, 2019)
There is an unclear relationship between Polycystic Ovary Syndrome and psychiatric disorders including anxiety and depression. We aimed to evaluate temperamental and personal characteristics of patients with PCOS. Fifty patients with PCOS and 41 healthy controls were included in the study. Hormonal and demographic characteristics were recorded after gynecologic and psychiatric evaluation. Socio-demographical Data Form, Beck Depression Inventory, Beck Anxiety Inventory and the Cloninger’s Temperament and Character Inventory were performed for all participants. Patients with Policystic Ovary Syndrome had significantly higher depression and anxiety scores when compared to the controls (p < 0.05). There were no significant difference in any of the subdimensions neither for temperament nor for character between patient and control groups (p > 0.05). Testosteron levels and the degree of hirsutism, LH/FSH ratio and body mass index of the patients did not have significant correlations with depression or anxiety scores or any of the Cloninger subdimentions (p > 0.05). However, there was a negative correlation between age and novelty seeking and age and reward dependence (r:−0.33, p:0.018; r:−0.295, p:0.037, respectively). This preliminary study showed no significant difference between patients and healthy controls regarding temperament and character. Patients had higher anxiety and depression scores. Further research is needed to enlighten this subject.